Republic of Moldova : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2011)
The progress made by Moldova toward achieving the Millennium Development Goals (MDGs) has not been uniform since 2007. Domestic economic and political crises are likely to undermine the achievement of several MDG targets set for 2010 and 2015. The goals were to reduce extreme poverty and hunger, achieve universal access to general secondary education, promote gender equality and empower woman, and so on. After growing dramatically in 1998-1999, poverty in Moldova began to decline in 2000. Addressing the environmental challenges and risks is imperative for Moldova.